Rotavirus Nosocomial Infection in Children under 5 years of age: A Preliminary study in Nepal - Sherchan, JB; Ohara, H; Sherpa, K; Sakurada, S; Gurung, B; Tandukar, S; Pradhan, L; Burlakoti, T; Pokharel, BM; Sherchand, JB (Journal of Nepal Paediatric Society, 2011)
Introduction: Rotavirus is one of the most common causes of acute gastroenteritis among infants and young children. The spread of rotavirus infection in pediatric wards can cause acute diarrhoea during hospitalization, and in turn, prolong hospitalization or need, rehospitalization. The aim of the study was to determine the prevalence of nosocomial infection due to rotavirus and other causal organisms among children less than 5 years of age. Methodology: A cross-sectional study between November 2009 and May 2010 was conducted among 96 pediatric patients in children hospital, Nepal. Stool samples were collected during hospitalization and up to 3 days after discharge from the hospital. Rotavirus antigens were detected by EIA and standard microbiological procedure were applied for other enteric pathogens. Results: The prevalence of nosocomial infection due to rotavirus was 30.2% (29/96). Of them, 16 (55.17%) of the 29 children with nosocomial infection during hospitalization and/or up to 72 hours after discharge developed diarrhoea. The prevalence of symptomatic cases of nosocomial infection was 55.17% (16/29), which involved 16.7% (16/96) of the study subjects, showing a prevalence of 44.82% (13/29) for asymptomatic nosocomial infection consisted of 13.54% (13/96) of the total subjects. Eleven of the 16 symptomatic subjects of nosocomial infection were affected by diarrhoea during hospitalization and five subjects after discharge. Bacteria (8.3%) and protozoa (5.2%) agents were also causing nosocomial infection in children. Conclusions: Children attending hospital may asymptomatically carry enteric pathogens and potentially act as source of nosocomial infection. Due to the relatively high frequency of nosocomial infection in the Children Hospital of Nepal, it is necessary to follow strictly hygienic rules such as isolation of patients with diarrhoea and hand-washing before and after the examination of each patient and cleaning the examination instruments after use in each patient. Key words: Diarrhoea; children; Rotavirus infection; Cross-sectional study; Nepal DOI: 10.3126/jnps.v31i1.3540 J Nep Paedtr Soc 2010;31(1):30-34